Credibilidad percibida del periodismo a través de la Internet: una visión desde la psicología del consumidor (2011)
This article describes some perceived credibility criteria that people use when judging Internet journalism. These criteria were compared with those found in the literature on journalism credibility in international contexts. With a sample of 166 participants who rated with a Likert scale, the perceived credibility that Colombian people have about Internet journalism was explored. Results show that there is agreement between the criteria found in the research literature and those used by online readers, however, was found a negative correlation between Internet dependence (professional/scholar) and the level of credibility as well as between changes in the level of credibility and some socio-demographic variables.